1997
DOI: 10.1007/s004390050534
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that skewed X inactivation is not needed for the phenotypic expression of Aicardi syndrome

Abstract: Aicardi syndrome is a rare disorder characterized by absent corpus callosum, infantile spasms, and choriorentinal lacunae. It is sporadic in nature and affects only females, resulting in severe mental and physical handicap. It has been suggested that the disease is caused by a dominant X-linked mutation which occurs de novo in females, and is lethal in hemizygous male embryos. This mode of inheritance has been observed in a number of other rare syndromes. In these syndromes, when X inactivation is studied, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The only three known males with a confirmed diagnosis have a 47,XXY karyotype [Hopkins et al, 1979;Aicardi, 1999]. The striking variable severity and asymmetry of the Aicardi syndrome phenotype could be explained if the putative mutated gene undergoes X-chromosome inactivation [Wettke-Schafer and Kantner, 1983]; however, the few limited studies show a general pattern of random X-chromosome inactivation [Wieacker et al, 1985;Neidich et al, 1990;Hoag et al, 1997]. Sequencing and deletion studies have demonstrated that Aicardi syndrome is not allelic to either Microphthalmia with Linear Skin Defects (MLS) or Goltz syndrome [Van den Veyver et al, 1998;Van den Veyver, 2002].…”
Section: Introductionmentioning
confidence: 98%
“…The only three known males with a confirmed diagnosis have a 47,XXY karyotype [Hopkins et al, 1979;Aicardi, 1999]. The striking variable severity and asymmetry of the Aicardi syndrome phenotype could be explained if the putative mutated gene undergoes X-chromosome inactivation [Wettke-Schafer and Kantner, 1983]; however, the few limited studies show a general pattern of random X-chromosome inactivation [Wieacker et al, 1985;Neidich et al, 1990;Hoag et al, 1997]. Sequencing and deletion studies have demonstrated that Aicardi syndrome is not allelic to either Microphthalmia with Linear Skin Defects (MLS) or Goltz syndrome [Van den Veyver et al, 1998;Van den Veyver, 2002].…”
Section: Introductionmentioning
confidence: 98%
“…Studies of XCI in AIC conducted in the past did not provide a definitive conclusion about X-chromosome inactivation status in AIC (Neidich et al 1990; Hoag et al 1997; Wieacker et al 1985). Our study demonstrates that skewing of XCI is present in a much higher number of affected girls than what would be expected, even though not all subjects have non-random patterns of XCI.…”
Section: Discussionmentioning
confidence: 98%
“…However, the evaluation of XCI in AIC has been limited by the small numbers of subjects studied and older methodology, and different studies have generated contradictory results. One investigation, that evaluated XCI by DNA methylation analysis at the androgen receptor gene in peripheral blood leukocytes of ten females with AIC and their parents, found that patients had a random XCI pattern (Hoag et al 1997). An isolated case report described a single girl with AIC and random XCI (Wieacker et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…A few XCI studies have been performed in Aicardi syndrome, but the data are not all in agreement. Some authors report skewed patterns (Neidich et al, 1990), while others report more random patterns (Wieacker et al, 1985;Hoag et al, 1997). This may be related to the fact that usually only DNA extracted from peripheral blood leukocytes, from epithelial cells of buccal swabs, or from skin fibroblasts is accessible for study.…”
Section: Chromosome Inactivationmentioning
confidence: 97%
“…The patterns of XCI in these tissues may not be representative of those in brain and eye, the primary organs affected in Aicardi syndrome. Furthermore, different methods for studying XCI have been used in the various studies: some investigators have applied the human androgen receptor assay (Allen et al, 1992;Hoag et al, 1997), while others have used methylation-sensitive restriction enzyme analysis (Neidich et al, 1990) and segregation of the active X chromosome in somatic cell hybrids (Wieacker et al, 1985;Neidich et al, 1990). In one set of monozygotic twins discordant for Aicardi syndrome, both have random patterns of XCI.…”
Section: Chromosome Inactivationmentioning
confidence: 99%